Strengthening Four Competencies of Teachers In Improving The Professionalism of MI/SD Educators (Personal, Social, Professional, And Pedagogical Competencies) - Alya Khoirunnisah; Sujenny Djeskyah; Sania Hairunnisak; Abdurrahmansyah Abdurrahmansyah (International Journal of Education, Information Technology, and Others, 2026)
Education plays a crucial role in developing human potential and improving the quality of national human resources. The success of education is strongly influenced by teachers as the main actors in the learning process. However, various studies indicate that teacher competencies in several schools remain inadequate, which affects the quality of learning and student achievement. This study aims to analyze the importance of strengthening the four core teacher competencies pedagogical, professional, personal, and social competencies in improving the quality of education at the elementary level (MI/SD). This research employs a qualitative approach using a literature review method. Data were collected from scientific journals, books, regulations, and relevant academic sources accessed through Google Scholar and other educational databases. The data were analyzed descriptively by identifying, categorizing, and synthesizing key findings related to teacher competencies. The results indicate that the four competencies are interrelated and play a significant role in enhancing teacher performance and learning quality. Therefore, continuous efforts to strengthen these competencies are essential to foster effective learning and to develop students who are intellectually capable and possess strong moral character.